Answer:
12g
Step-by-step explanation:
I don't have a lot of contexts here but based on what saw the answer should be 12g
Answer:
x=6, x=-5
Step-by-step explanation:
Factoring this quadratic gets you (x-6)(x+5)=0, for this to be possible, either x-6 or x+5 has to be zero, so therefor x is 6, or x is -5
<span>1/6 (12C + 24) + 1/3(12 c - 3) =
12 c/ 6 + 4 +12c / 3 - 1 =
2c +4 + 4 c -1
6c +3 </span>
8+6/2=17-5
We can start by reducing the fraction using basic division.
Remember, numerator divided by denominator.
6 \ 2 = 3.
Rewrite the equation-
8+3=17-5
It doesn’t matter which side of the equal sign you start with, but in this case I started with the right hand.
8+3= 11
Rewrite-
11=17-5
Now subtract.
17-5=12
Write the equality.
11=12.
This is false.
11≠12.